Experience of Some Countries of The Commonwealth of Nations in Ensuring Criminological Protection of Justice - Yuliia Khrystova; Oleksiy TitarenkÐ¾; Oleksandr Cherviakov; Oleksandr Marushchak; SerhÑ–i ShkolÐ° (UIN Sunan Gunung Djati, 2024)
The article describes the experience of Great Britain, Canada, Australia, and New Zealand in the field of criminological protection of justice. A combination of philosophical, general scientific and specific scientific research methods was used in the preparation of this article to find out which special actors are authorized to carry out such criminological activities, to analyze the powers and guarantees for their exercise to fulfill their tasks. The article reveals the peculiarities of interaction of special actors of ensuring the security of justice with other actors in the system of combating offenses and crimes against justice. The author emphasizes the role of the sheriff, police, and private security companies in ensuring security during the judicial process. The experience of these Commonwealth countries in identifying and counteracting possible threats to the security of justice is analyzed. The purpose of this work was to single out positive foreign experience that may be promising for implementation into the national legislation with the aim of improving activities of the Court Security Service, which is a special subject performing implementation of the function of criminological protection of justice in Ukraine. In particular, firstly, to find out which special entities are authorized to carry out the specified criminological function in certain countries of the British Commonwealth and what powers they have; secondly, what other law enforcement agencies are involved in the mechanism of ensuring criminological protection of justice and what are the features of their interaction with special subjects; thirdly, what measures they take to detect and counter possible threats to the security of justice.